Limitations of Islamic Book Collection in Fulfill Al Kautsar Islamic Boarding School Library - Rika Jufriazia Manita; Marteen Dovick; Curthin Lewis Buer (Alfuad: Jurnal Sosial Keagamaan, 2023)
This research emphasizes the limitations of Islamic book collections in meeting the information needs of users at the Al Kautsar Muhammadiyah Islamic Boarding School Library, Lima Puluh Kota Regency. The purpose of the study was to determine the level of user satisfaction with the provision of Islamic book collections at the Al Kautsar Muhammadiyah Islamic Boarding School Library in Lima Puluh KotaRegency and to determine the suitability of existing Islamic book collections with the information needs of users at the Al Kautsar Muhammadiyah Islamic Boarding School Library in Fifty Cities. In this study using a qualitative descriptive type of research, the research informants are librarians and users of the Al Kautsar Muhammadiyah Islamic Boarding School Library, Lima Puluh Kota Regency. The data collection method that the author uses is observation (observation), interviews, and documentation (archiving). In analyzing the data using data analysis Miles and Huberman. The results of this study found that the Santri of the Modern Islamic Boarding School Al Kautsar Muhammadiyah District of Lima Puluh Kota was not satisfied with using the collection of Islamic books served by the library because the information obtained was insufficient for the information needs of users. Currently, the collection of Islamic books has varied and varied, but the number of collections of Islamic books has not met the needs so there is no satisfaction for users in finding the information they need. Many collections of Islamic books in the Al Kautsar Muhammadiyah Islamic Boarding School Library in Lima Puluh KotaRegency are outdated and no longer up to date. To add to the collection of Islamic books, the latest publications have not yet been held, resulting in users being dissatisfied with the information in the library.